Characterization of the Schizosaccharomyces pombe ral2 gene implicated in activation of the ras1 gene product. - Fukui, Y (1989)
Mutations in the Schizosaccharomyces pombe ral2 gene cause a phenotype indistinguishable from that of the ras1-defective mutant. Using cloned ral2 DNA, we disrupted the chromosomal gene. The disruptants showed the same phenotype as the original ral2 isolates, i.e., they had spherical cells, had no detectable mating activity, and exhibited no response to the mating pheromone, but their vegetative growth was apparently normal. Sequence analysis of the ral2 gene suggests that it encodes a polypeptide of 611 amino acid residues whose predicted amino acid sequence shows no strong homology to any known protein. Either multiple copies or even a single copy of the ras1Val-17 allele, which is an activated form of ras1, restored rodlike cell morphology and ability to respond to the mating factor to ral2 mutants. These results suggest that the ral2 and ras1 gene products interact intimately and that the ral2 gene product is involved in activation of the ras1 protein in S. pombe.